Fundus Changes Evaluated by OCTA in Patients With Cerebral Small Vessel Disease and Their Correlations: A Cross-Sectional Study - Fu, Wang; Zhou, Xiaoyu; Wang, Minli; Li, Ping; Hou, Jingjing; Gao, Peng; Wang, Jue (Frontiers in Neurology, 2022)
Objective To detect fundus changes in patients with cerebral small vessel disease (CSVD) using optical coherence tomography angiography (OCTA) and to investigate the correlations between CSVD and fundus changes. Methods From January 2019 to January 2020, patients diagnosed with CSVD by magnetic resonance imaging (MRI) were enrolled in our study and received fundus examinations using OCTA. CSVD was defined as white matter hyperintensities, enlarged perivascular spaces, lacunes, or microbleeds on MRI. OCTA parameters included foveal avascular zone areas, retinal nerve fiber layer thickness, and capillary densities of the superficial retinal capillary plexuses, deep retinal capillary plexuses, and the radial peripapillary capillary network of the disc. Univariate and multivariate logistic regression analyses were performed to explore the correlation between CSVD and fundus changes. Results A total of 115 patients (40% male) were enrolled and analyzed, and the mean age was 65.11 ± 11.23 years. After multivariate logistic regression analysis, the radial peripapillary capillary network density was negatively correlated with severity of deep white matter lesions (OR: 0.909; 95% CI: 0.828–0.998; p = 0.046) and perivascular spaces (OR: 0.881; 95% CI: 0.779–0.995; p = 0.041). Parafoveal vessel densities of the superficial retinal capillary plexuses were independently correlated with lacunes (OR: 0.889; 95% CI: 0.817–0.967; p = 0.006). Conclusion OCTA parameters were correlated with CSVD, indicating that OCTA is a potential method for CSVD screening.